2016
DOI: 10.1039/c6nj02107g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted hydrothermal synthesis of UV-emitting carbon dots from tannic acid

Abstract: UV-photoluminescent carbon dots were synthesized through a facile process and were used as fluorophores for the highly selective and sensitive detection of picric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 61 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…The lifetimes had almost no change in the presence of MnO 4 − , which indicated that the static quenching effect (SQE) was formed between N/P CDs and MnO 4 − . In the RET process, target molecules can significantly change the fluorescence lifetime of the fluorophore ( Joseph and Anappara, 2016 ; Liu et al, 2016 ; Sun et al, 2016 ; Li et al, 2018 ). Thus, RET was not the main reason to induce the fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
“…The lifetimes had almost no change in the presence of MnO 4 − , which indicated that the static quenching effect (SQE) was formed between N/P CDs and MnO 4 − . In the RET process, target molecules can significantly change the fluorescence lifetime of the fluorophore ( Joseph and Anappara, 2016 ; Liu et al, 2016 ; Sun et al, 2016 ; Li et al, 2018 ). Thus, RET was not the main reason to induce the fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution O 1s spectra are shown in Figure 6 c,g,k,o. The two fitted peaks at 531.3 and 532.4 eV are ascribed to C=O and C–O groups [ 74 , 75 ], respectively. The existence of C–O and C=O bonds indicated that the surface of the as-synthesized CQDs is functionalized by multiple oxygenated groups, which is consistent with C1s spectra.…”
Section: Resultsmentioning
confidence: 99%
“…As the optoelectronic properties of CDs are strongly dependent on emissive sites of the surface functional groups, unlike other fluorophores, carbon dots exhibit excitation wavelength‐dependent emission. Although excitation‐wavelength dependent/independent fluorescence emission at different spectral ranges was realized with CDs, reports regarding phosphorescence from CDs are rather rare …”
Section: Figurementioning
confidence: 99%